(untitled) (Estudios humanísticos. Geografía, historia y arte, 2021)
Artists have always travelled. But aboye all during their youth, searching to complete their apprenticeship. Howcver, our century has change the meaning of thar travel, doing it frequent, not only during formation years, but along all life. The internationalitation of artistic language imposes it